Encoding Art Against Accurate Communication. Andrzej Partum’s Poems and Manifestos - Rejniak-Majewska, Agnieszka ((Dif)fusions: Relations between Literature and Art in Poland after 1945, 2019)
The text is devoted to the creative activities of Andrzej Partum, in particular his specific approach to language, which is evident in his early volumes of poetry from the 1960s and later manifestoes. Partum’s poetry presents itself a selfconscious play with language, intellectual and epistemic provocation, marked by unbelief in the sense-giving and ordering power of language. This makes a connection with the style of his later ‘programmatic texts’ and manifestoes in which the individual act of speech is above all a gesture, a form of interpellation and a question directed towards the recipient, not a consistent message with specific content. The object of analysis is both the reception of Partum’s work in the contemporary literary world in Poland and in the circles of independent art which in the ‘70s were assimilating and redefining the ideas of conceptual art. Whereas within the literary field Partum’s activity was perceived only as an intriguing but difficult to assess peculiarity, due to the specific conceptual and institutional structures of this field, in the milieu of multi-media, contestatory art, its myth-generating potential was more fully developed and appreciated. It was, as I argue, the result of Partum’s emphasis on the eventual, situational and personal dimension of communicative acts.